2004
DOI: 10.1063/1.1699493
|View full text |Cite
|
Sign up to set email alerts
|

On the bowing parameter in Cd1−xZnxTe

Abstract: Cd 1−x Zn x Te thin films were prepared on 7059 Corning glass substrates using an rf magnetron sputtering system and CdTe(1−y)+ZnTe(y) targets. The concentration (x) of Zn in the films did not coincide with the relative weight (y) of the ZnTe powder in the compressed targets. Values of x were in the range 0–0.30 as determined from x-ray diffraction patterns. The band gap energy (Eg) of the Cd1−xZnxTe samples was calculated from the photoreflectance spectra measured on the films. The position of the experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 34 publications
1
10
1
Order By: Relevance
“…Zn = 0.20% and 0.25%). It is contrary for the reported results [24]. However, the peak sharpness is found to decrease with increasing zinc content.…”
Section: Transmittance Studiescontrasting
confidence: 74%
“…Zn = 0.20% and 0.25%). It is contrary for the reported results [24]. However, the peak sharpness is found to decrease with increasing zinc content.…”
Section: Transmittance Studiescontrasting
confidence: 74%
“…For both of these data sets, the bandgap energy is seen to increase almost linearly with composition over the entire range of 0 ≤ x ≤ 1 and , therefore, the bowing parameters are found to be very small. At room temperature (RT), Zelaya-Angel et al [34] reported their photo-reflectance measurements on CdZnTe thin films grown by the sputtering technique. Although raising the the temperature usually causes a reduction in the bandgap energy, the bowing, as reported by these authors [34], remains limited and small (b = 0.10 ± 0.01 eV).…”
Section: Tablementioning
confidence: 99%
“…At room temperature (RT), Zelaya-Angel et al [34] reported their photo-reflectance measurements on CdZnTe thin films grown by the sputtering technique. Although raising the the temperature usually causes a reduction in the bandgap energy, the bowing, as reported by these authors [34], remains limited and small (b = 0.10 ± 0.01 eV). Our calculated bandgap energies for the same alloys are shown in Fig.…”
Section: Tablementioning
confidence: 99%
“…The value of E g at liquid-helium temperature is well established as 1.606 eV. But discrepancies for the reported value of E g at room temperature (RT) are large, ranging from 1.49 to 1.53 eV, as summarized by Lee et al [1] and Zelaya-Angel et al [2]. It seems that the actual generally accepted value of E g is 1.512 ± 0.003 eV, as deduced from photoreflectance and electroreflectance methods [1,3].…”
Section: Introductionmentioning
confidence: 96%